Is online treatment adherence affected by presentation and therapist support? A randomized controlled trial. (July 2016) - Alfonsson, Sven; Olsson, Erik; Linderman, Sara; Winnerhed, Sofia; Hursti, Timo
Abstract: In both face to face and Internet based Cognitive Behavior Therapy, patients' adherence can be improved by different means such as by using motivational techniques or automatic reminders. The main aim of this study was to investigate whether enriched treatment material presentation and/or increased frequency and quality of support would increase participants' adherence to an online relaxation program. One hundred and sixty-two participants with mild to moderate symptoms of stress or worry were included in this study. Participants were randomized to either Normal or Enhanced intervention presentation and Normal or Enhanced support in a full factorial design. Main outcome variables were progress through the online intervention and adherence to prescribed exercises. Participants in the Enhanced support group progressed further through the program than participants in the Normal support group ( Z  = 2.11, p  = .035, r  = .17) but there were no significant differences found between the Normal and Enhanced presentation groups. Participants registered a mean of 60% of the prescribed exercises with no significant differences between groups. This study shows that adherence to online interventions can be increased by increased frequency and quality of therapeutic contact. Future studies may investigate how to increase adherence to prescribed homework assignments and whether parts of the therapeutic support may be substituted with automatic systems with retained effects. Highlights: Presentation and support of online CBT was enhanced to assess effects on adherence. Enriched presentation did not affect participants' adherence to treatment. Enhanced therapeutic support did increase the completion rate of the CBT program.